Distance Learning: Does it Have an Impact on the Readiness of Physical Education Teachers in Coastal Areas? - Ermawan Susanto; Farida Mulyaningsih; Mujriah Mujriah; Rabwan Satriawan; Sulfandi Sulfandi (OVS LLC, 2022)
Study purpose. The purpose of this study was to determine whether there is an effect of distance learning on the readiness of physical education teachers in coastal areas. Materials and methods. This study used an experimental method with one group pre-test-post-test design. The research participants were physical education teachers in junior high schools in coastal areas (n = 60). Primary data collection to measure teacher readiness was the Online Teaching Readiness Survey consisting of 41 questions with a validity level of 0.76 and a reliability of 0.91. Secondary data collection was performed using literature study. Results. The results of the paired sample t-test showed 0.754 > 0.01, indicating the data variance was the same. By looking at the assumed equal variances, the significance result shows that .000 < .01 (confidence interval = 99%), then H0 is rejected. Based on the data, there are 10 teachers or 16% who are ready to carry out distance learning, 36 teachers or 60% are not ready, and 14 teachers or 24% are unprepared. Conclusions. There is an impact of distance learning on the readiness of PE teachers in coastal areas. The effect in question shows the unpreparedness of PE teachers in implementing distance learning. The recommendation from the findings is that teachers need virtual learning training and adequate support to succeed in distance learning.